Geomechanics and Geophysics for Geo-Energy and Geo-Resources - Elsworth, Derek; Huppert, Herbert; Li, JianChun; Ranjith, P.G.; Xie, Heping; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
The journal Geomechanics and Geophysics for Geo-Energy and Geo-Resources (G4) publishes original research, new developments, and case studies in the field of geomechanics and geophysics with special application to energy and resources in the subsurface Earth. This covers the full scope of geomechanics and geophysics including theory and analysis, laboratory and field experiments, numerical methods and modelling techniques, and engineering applications and technology development related to energy and resources. This scope includes discovery and recovery of conventional and unconventional hydrocarbons, mining and resources engineering, natural and enhanced geothermal energy, geotechnical engineering of energy storage, geological solutions for energy and resources including geological disposal of energy wastes including sequestration of carbon dioxide. All papers on these topics within the journal scope are welcomed.
Keywords: Engineering geology; Geotechnical engineering; Geophysics; Electric power production; Renewable energy sources; Environment; Geoengineering; Geotechnical Engineering and Applied Earth Sciences; Geophysics; Electrical Power Engineering; Renewable Energy; Environmental Sciences